(untitled) (Altre Modernità, 2021)
In 2003 the final report of the Truth and Reconciliation Commission TRC of Peru concluded that the most probable number of fatalities during the last two decades of the 20th century exceeded 69 thousand peruvians killed or disappeared at the hands of subversive organizations or by agents of the State. The philosopher and professor Mario Montalbetti, a member of the TRC, issued two reports, one verbal and the other visual, and the gap between the two generated epistemological and political questions regarding the general status of the truth about the violence suffered in those years in Peru «Where was the meaning of what happened? Was it found in the word that testified or in the image that moved? What was each of the two reports trying to communicate? What discourse of memory appears in these? What type of language is chosen to give an account of what happened and to build a story according to the experience of the victims? » (Montalbetti 147). Taking these questions as a premise, I am interested in analyzing two visual archives that bear witness to the horror experienced in Peru during the last two decades of the 20th century: The Retablos de Sendero Luminoso and The transmedia photography project Yuyanapaq. I will try to comment on these two visual archives of memory following the particular contribution to the project of an ethics ’after Auschwitz’ that Giorgio Agamben makes in his evocative reconsideration of testimony as an ethics of witnessing the collapse of the human and inhuman. The speech of testimony is instead best named ethical. I will demonstrate how these visual archives of memory have contributed to re-politicize and to perform a society that is recognized as a collective of equals, a little step in the search for a reconciliation apparently still distant.